PREPARATION OF BALLOT PAPERS FOR PRESIDENT AND VICE PRESIDENT ELECTIONS IN THE 2024 ELECTION - Erin, Ni Putu; Widhiasthini, Ni Wayan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
"General Election" or often known as "Election" is a means of exercising people's sovereignty which is held every five years directly, publicly, freely, secretly, honestly and fairly. The main element that supports the successful implementation of elections is logistics, especially ballots for the President and Vice President. The purpose of this community service is to find out the preparation of ballots for the President and Vice President Elections held in Sesetan Village. The implementation method consists of five stages, namely 1) Ballot preparation, 2) Ballot distribution, 3) Ballot Casting, 4) Reception of Ballots, 5) Recapitulation of Ballots. The results of these stages show the occurrence of several obstacles such as the preparation and packing process is feared to spend a long duration due to the large number of voters and the number of polling stations (TPS), but after the division of tasks and responsibilities these obstacles can be anticipated.